Instabilities of visual perception in the 'Bath Series' of Jasper Johns (1983-1988) - Smit, Susanna Margrietha (My University, 2012)
The ‘Bath Series’ (1983-1988) of Jasper Johns shows the artist’s meditation on his oeuvre of the past thirty years, and the examples of his previous works demonstrate his interest in instabilities of visual perception. The latter are activated when the viewer’s expectation to see conventional representational strategies are destabilized, and figure/ground pictorial space, particularly, becomes ambiguous. This first recorded academic study focusing exclusively on the series as a unit, discovers that figure/ground switching, an ‘Ur-Gestalt’ (Gandelman 1989: 209), appears to be a core energy motivating ambiguous pictorial space in Johns’ art, and constitutes the theoretical component of the research. The practical component is a site specific installation which shows some visual and verbal processes and meditates on the perpetual interaction between the eye and the mind, which is a fundamental concern of Johns (Varnedoe 1996b: 245, 257), as well as of myself. The work invites viewers to experience destabilized conventional visual perceptions and to explore, as Johns said, ‘something new’ (Varnedoe 1996a: 17).
M.A.University of the Witwatersrand, Faculty of Humanities (Fine Arts), 2012
Keywords: visual perception; metastability; spatial ambiguity; figure/ground; verbal/visual processing